Low velocity impact response of kenaf/epoxy composites exposed to corrosive solutions / Abdul Hakim Abdullah ... [et al.] - Abdullah, Abdul Hakim; Hamid, Nur Intan Natrah Aqilah; Solihin, Zainoor Hailmee; Abd Ghani, Muhd Azimin; Adull Manan, Nor Fazli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Kenaf fibres are one of the natural fibres that have been widely explored since the fibres are low in cost, have excellent mechanical properties and biodegradability features. Recently, there have been numerous efforts to employ kenaf fibres reinforced composites in a wide range of applications. One of the concerns is that these composites may be exposed to several ranges of corrosive conditions during their in-service life and their durability performance is extremely necessary. Therefore, the aim of this work is to study the mechanical response subjected to flexural and low velocity impact tests of kenaf/epoxy composites with a variety of corrosive solutions, after being exposed to hydrochloric acid (HCl) and sodium hydroxide (NaOH) solutions for durations of 12, 24 and 36 days. The experiment result demonstrated that the corrosive solutions have a detrimental effect on the flexural properties and impact response of composites. The degradation effect on composites is also found to be dependent on the exposure period in the corrosive solutions. On the other hand, acidic environments have been shown to have a more aggressive effect on the performance of composites than an alkaline environment.